Pollen spectra among natural populations of Apis cerana Fabricius in the Philippines - Tilde, A. C.; Payawal, P. C; Cervancia, C. R. (2003)
The pollen spectra of natural populations of the honey bee (Apis cerana Fabricius) were determined. Forty-one families of flowering plants were identified and pollen pellets from 101 colonies of A. cerana were collected from various areas of the Philippines. The major pollen types were Leucaena leucocephala (Lam.) de Wit, Mimosa diplotricha Mart. ex Sauvallo, Mimosa pudica L., Callistemon citrinus (Curt.) Stapf, Zea mays L., Cocos nucifera L., Pterocarpus indicus Wild., Muntingia calabura L. and unidentified species of the family Ulmaceae. The pollen spectra of honey bees were generally homogeneous. Only the samples from Baguio and Benguet (Luzon highland) were distinct, characterized by the presence of species that grow well in colder areas. Diversity of the pollen spectra had no relation with geographical origin.
Keywords: Bee culture; Pollen